IST KSRA Draft Proposal: Reading Assessment Instrumentation. - Instructional Support System of Pennsylvania, East Petersburg; Instructional Support System of Pennsylvania, East Petersburg ([S.l.] : Distributed by ERIC Clearinghouse, 1994)
Bringing structure to the reading assessment process, this paper presents a draft proposal of an assessment structure which practitioners can follow, one which can be applied systematically within the Instructional Support Team process across Pennsylvania. After some background information, the paper briefly discusses features of effective reading assessment, suggesting that effective reading assessment needs to be continuous, multidimensional, authentic, student centered, and performance based. The paper then presents an evaluation form for reading assessment domains. It next discusses 14 points to remember or clarify in developing the instrumentation. The paper then outlines the 3 steps of the proposed instrumentation (entry, selecting materials, and sampling). A description of how to compile running records of students' reading processes is attached. (RS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alternative Assessment; Elementary Education; Performance Based Assessment; Reading Achievement; Reading Tests; Teaching Guides; Test Construction; Test Format; Pennsylvania -- Student Centered Assessment; Guides, Classroom -- Teacher; Opinion Papers